PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY DAN METAVERSE UNTUK MENINGKATKAN KINERJA GURU SMA/SMK/SLB DI PROVINSI SUMATERA SELATAN - Leon A. Abdillah; Rezania Agramanisti Azdy; Yeni Ernawati; Aan Restu Mukti (LPPM Universitas Andalas, 2024)
The purpose of this activity is to look at the design and implementation of an innovative learning media for high school (SMA/SMK) and special needs (SLB) teachers in South Sumatra, with a focus on the integration of Augmented Reality (AR) and the growing notion of the Metaverse. Traditional teaching methods are developing to accommodate the different requirements of students as technology advances, and this project tries to bridge the gap by offering cutting-edge technologies to instructors. The activity method used is a combination of lectures and workshops. The study digs into the creation of a learning media platform that uses augmented reality and the Metaverse to improve teaching tactics and engage students in a more immersive and interactive learning environment. Teachers can develop dynamic classes that go beyond traditional classroom experiences by mixing various tools, fostering a deeper grasp of complicated subjects. The influence of this augmented learning strategy on student engagement, information retention, and overall educational outcomes is discussed in the essay. Furthermore, it explores the obstacles and opportunities involved with integrating AR and the Metaverse into the South Sumatra educational scene, providing insights for educators, policymakers, and stakeholders striving to improve educational quality through technology innovation. This study adds to the continuing discussion about the transition of education in the digital era, with a focus on the local context of South Sumatra. The results obtained are increased understanding among teachers regarding the use of AR and Metaverse in learning at the SMA/SMK/SLB level.